Solusi Al-Qur’an dalam Mengatasi Pengaruh Media Sosial TikTok Terhadap Keagamaan Generasi Muda - Fikrianoor, Ardiyan; Ishaac, Muhamad (Jurnal Keislaman, 2024)
This research aims to determine the influence of TikTok social media on the religion of the younger generation from the perspective of the Koran. This research was conducted using the library research method, which includes analysis of literature such as the Al-Qur'an, hadith, journals, and related books. In the digital era, social media has become an important platform for the younger generation to express themselves and seek information. TikTok, as a popular application, allows users to create short videos with various interesting effects. However, its inappropriate use can have negative impacts, such as reducing valuable time, reducing a culture of shame, and spreading hoax news. This research found that TikTok has a significant effect on the religion of the younger generation, including the potential for antisocial behavior, wasting time, and decreasing Islamic values. To overcome these negative influences, the Qur'an provides important guidance, including commands to socialize well, make the best use of time, and maintain a culture of shame. This article offers a unique perspective on how the younger generation can use social media wisely and still retain their religious values ​​through the teachings of the Koran. Thus, it is hoped that this research can provide practical and theoretical benefits for the younger generation and the general public in overcoming the challenges of using social media in the digital era.